Studi Komparasi Antara Strategi Learning Start With A Question Dengan Giving Question and Getting Answer Pada Hasil Belajar IPA Siswa Kelas IV SD Muhammadiyah 23 Semanggi Surakarta Tahun 2015/ 2016 - HIDAYATI, LUTHFIAH, Drs. Mulyadi, SH.,M.Pd (2016)
ABSTRACT Luthfiah Hidayati/A510120188. COMPARISON STUDY BETWEEN STRATEGY OF LEARNING START WITH A QUESTION WITH GIVING QUESTION AND GETTING ANSWER OF THE SAINS LEARNING OUTCOMES IN STUDENT FOURTH GRADE SD MUHAMMADIYAH 23 SEMANGGI SURAKARTA IN 2015 / 2016. Thesis, the Faculty of Education, University of Muhammadiyah Surakarta. April, 2016. This study aims to determine (1) Whether there is any difference in learning outcomes science between use strategies Learning start with a question to the strategy Giving Question and Getting Answer fourth grade student of SD Muhammadiyah 23 Surakarta, (2) the strategy which is better learning outcomes between strategies Learning start with a question to the strategy Giving Getting Question and Answer fourth grade students of SD Muhammadiyah 23 Semanggi Surakarta academic year 2015 / 2016. This type of research is quantitative research experiment. Sample of this research is class IVA with a number of 31 students. The method used for data collection was a test and documentation. Data analysis technique using a hypothesis test or t test. Be base on data analysis with significance level of 5% values obtained thitung 2.221> ttabel2.000 to the mean result of learning to use strategies Learning Start with a Question higher than that of learning to use strategies Getting Giving Question and Answer namely 76.62> 68.87. The conclusion in this study were 1) There is a difference between the effects of learning outcomes IPA using Start Learning strategy with a question by using the strategy of Giving Question and Answer Getting the fourth grade students of SD Muhammadiyah Surakarta 23 Semanggi 2015 / 2016. With this conclusion, the first hypothesis rejected because t> dk with a value of 2,221> 2,000. 2) Results of Science learning by using Learning strategy Start with a Question better than strategy Giving Getting Question and Answer. Reviewed fourth grade students of SD Muhammadiyah Surakarta 23 Semanggi 2015 / 2016. This can be ascertained from the difference in the average student learning outcomes, namely 76.61> 68.89. Keywords: comparative, giving question and getting answer, learning outcomes, learning start with a question.